Comparative evaluation of microleakage and hardness of newer posterior restorative materials - Anjali Sardana; Mohit Kumar; Sonali Taneja (Elsevier, 2022)
Background: The physical properties of restorative materials are critical when restoring posterior teeth. Restorative materials are continuously evolving in the quest for creating long lasting restorations. Aim and objective: To compare and evaluate microleakage and hardness of three different posterior restorative materials: Cention N, Zirconomer Improved and Solare Sculpt. Materials and methods: For micro leakage evaluation, 40 extracted human third molars were randomly divided into three experimental groups of 10 teeth each and two control group of 5 teeth each. Standardized box shaped class II cavity preparation was done in Group I, II, III and V. In Group V, cavity was prepared but left unrestored. No cavities were prepared in Group IV. Cavities in Group I, II, and III were restored with Cention N, Zirconomer Improved, Solare Sculpt respectively. Teeth were thermocycled together for 500 cycles. All the samples were placed in 2% methylene blue for 24 h. Microleakage evaluation was done using stereomicroscope. For hardness evaluation ten standardized discs of each material were prepared and evaluated using vicker's hardness test. Results: All the groups showed some amount of microleakage. The mean micro-leakage score was significantly more among Group II compared to Group I. There was no significant difference in mean micro-leakage score between Groups I and III. The mean hardness value was significantly more among Groups I and II compared to Group III. Conclusion: No material was able to completely eliminate microleakage. Cention N showed high hardness among the materials tested.